The Israeli Nationality Law: A Blueprint for a Twenty-first Century Settler-Colonial State - Pappé, Ilan (Journal of Holy Land and Palestine Studies, 2019)
This article examines the recent Israeli Nationality Law within a historical context. It argues that the law in many ways manifests the settler-colonial identity of the State of Israel and as such ...